Arrosive bleeding from the cystic artery to the abdomen in elderly woman with acute gangrenous perforated calculous cholecystitis - A.V. Kapshitar; A.A. Kapshitar; V.Yu. Erokhin (Zaporozhye State Medical University, 2013)
Abstract The 82 years old patient was admitted to the general surgery clinic with complaints of severe abdominal pain, dry mouth, weakness. 3 hours before sharp pain had appeared in the epigastric region and spread to the right side of the abdomen. Pulse was100 BPM. Abdomen was greatly increased, painful in all regions, sharply and with tension in the epigastric region and right half. Shchetkin symptom was positive. Dullness on percussion. Intestinal peristalsis was absent. Survey radiography of the abdomen was normal. Hb - 137 g/l, Er - 4,45×1012/l, L - 14, 6x109/l, stabneutrophils - 23%. Diagnosis: «Perforated duodenal ulcer. Acute calculous cholecystitis? Diffuse peritonitis». Ultrasonography - gallbladder 11×5,3 сm, moderately swollen wall, filled with calculi. Diameter of common bile duct was 0,6 сm. In 2 hours after preparation the upper midline laparotomy was performed. Acute gangrenous ruptured calculous cholecystitis, bleeding into the abdominal cavity from the anterior branch of the cystic artery, grade 2 haemoperitoneum, stage 3 of shock, cirrhosis of the liver were diagnosed. Cholecystectomy from the neck, sanitation and drainage of the abdominal cavity were performed. The postoperative course was uneventful. The case shows the difficulties of clinical, laboratory and radiation diagnostics in establishing therare complication before the operation.